WVJ 2022
DOI: 10.54203/scil.2022.wvj52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ascorbic Acid on Maturation Rate, Morphology, and Gene Expression of Vitrified In Vitro Matured Dromedary Camel Oocytes

Abstract: In vitro embryo generation, cryopreservation, and embryo transfer are examples of assisted reproductive technologies that can be used to improve camel genetic performance and fertility. The aim of this study was to investigate the impact of ascorbic acid supplementation to in vitro maturation media on the maturation rate, morphology, and gene expression of fresh and vitrified in vitro matured dromedary camel oocytes. In the current study, 810 oocytes of excellent and good quality were in vitro matured in matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, studies have shown that melatonin, a potent antioxidant and free radical scavenger, can help reduce ROS levels in oocytes. This has been observed in pig (58), buffalo (34), bovine (57), and camel (11) species. Additionally, melatonin helps maintain adequate levels of endogenous antioxidant enzymes (59) and boosts the level of the antioxidant glutathione (GSH) (60).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, studies have shown that melatonin, a potent antioxidant and free radical scavenger, can help reduce ROS levels in oocytes. This has been observed in pig (58), buffalo (34), bovine (57), and camel (11) species. Additionally, melatonin helps maintain adequate levels of endogenous antioxidant enzymes (59) and boosts the level of the antioxidant glutathione (GSH) (60).…”
Section: Discussionmentioning
confidence: 62%
“…Cryopreservation can cause signi cant damage to both oocytes and embryos, with the oocyte membrane being the primary site of damage (57). Vitri cation can lead to hardening of the ZP of oocytes, which can signi cantly impact their ability to develop (57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that mammalian oocytes are very sensitive to temperature and osmotic pressure changes due to their complex subcellular structure [56]. Cryopreservation can cause significant damage to both oocytes and embryos, with the oocyte membrane being the primary site of damage [57]. Vitrification can lead to hardening of the ZP of oocytes, which can significantly impact their ability to develop [57].…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation can cause significant damage to both oocytes and embryos, with the oocyte membrane being the primary site of damage [57]. Vitrification can lead to hardening of the ZP of oocytes, which can significantly impact their ability to develop [57]. However, studies have shown that melatonin, a potent antioxidant and free radical scavenger, can help reduce oocyte ROS levels.…”
Section: Discussionmentioning
confidence: 99%